Hikmat Menurut Kitab Yakobus [Wisdom in the Book of James] - Suriani Sukowati Arifin (Diligentia: Journal of Theology and Christian Education, 2019)
James in his epistle teaches the readers to ask God for wisdom when experiencing difficulties or trials. God as the source of wisdom generously gives wisdom to anyone who asks in faith. Wisdom from pure God bears the character of a holy and gentle God. Believers need to realize that they need wisdom so they have to ask for wisdom by truly believing and depending on God. Wisdom from God is evident in the way of believers’s life on how they act, behave and assess problems, understand God's plan, and take the right action. The results of God's wisdom for the lives of believers are the sanctified life, kindness, peace and blessing.